A Comparative Assessment of the Proximate Composition, Ascorbic Acid and Heavy Metal Content of Two Species of Garden Egg (Solanum gilo and Solanum aubergine) - Edem; A., Christopher; Dosunmu; I., Miranda; Bassey; I., Francisca; Wilson; Charles; Umoren; Patience (Pakistan Journal of Nutrition, 2009)
The proximate composition ,ascorbic acid and Heavy metal contents of two species of Garden egg, Solanum gilo and Solanum aubergine were evaluated using chemical analysis. The result of the proximate composition analysis showed that solanum gilo fruits had the following composition:moisture (74.80%), carbohydrate (52.13%), crude protein (14.87%), crude fibre (16%), crude fat (7%) and ash (10%). It also contained (93.7%) of ascorbic acid. The Solanum aubergine fruits on the other hand contained moisture (94.6%), carbohydrate (58.5%), crude protein (15.75%), crude fat (4%), crude fibre (11.75%) and ash (10%). It also contained (75.9%) ascorbic acid. The Heavy metal concentrations of Solanum gilo fruits are Zn (3.81ppm), Cr (1.74ppm), Cd (0.16ppm), Cu (1.48ppm), Co (0.12ppm) and Hg (0.01ppm). The solanum aubergine fruits on the other hand contained Zn (1.58ppm), Cr (2.45ppm), Cd (0.77ppm), Cu (0.04ppm), Co (0.10ppm) and Hg (0.01ppm). The concentrations of As and Pb in the fruits of both species were not detected. The result Shows that the values of moisture, ascorbic acid, crude fibre and crude fat were higher in S. gilo fruits, while the values of carbohydrate and crude protein were higher in S. aubergine fruits. The result also showed that the fruits of both species have same ash content. The result revealed that the concentrations of Zn, Cu and Co were higher in S. gilo fruits, while S. aubergine fruits has higher values of Cr and Cd. The results also revealed that the concentrations of Cr and Cd in both species of the plant were all above WHO permissible limits of 0.05ppm and 0.005ppm, respectively.